Electrochemical Studies on the Corrosion Behavior of Common Metals in Eutectic Ionic Liquids - Alhasan, Rami (2017)
A Master of Science thesis in Chemical Engineering by Rami Alhasan entitled, "Electrochemical Studies on the Corrosion Behavior of Common Metals in Eutectic Ionic Liquids," submitted in May 2017. Thesis advisor is Dr. Taleb Ibrahim and thesis co-advisor is Dr. Nabil Abdel Jabbar. Soft and hard copy available.